STRES AKADEMIK DAN KEJADIAN GASTRITIS PADA REMAJA - Ignatia, Joanne Evansha; Neri, Ervina Lili; Fauzan, Suhaimi (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Academic is an activity related to teaching and learning activities at an educational institution, such as a high school. Teenagers who become students at high school institutions can certainly experience academic stress caused by the workload, long study time, and high demands for achievement. Academic stress can be one of the factors that cause gastritis so that it causes signs and symptoms, such as decreased appetite, heartburn, bloating and sour taste in the mouth. The purpose of this study is to determine the relationship between the level of academic stress and the incidence of gastritis in adolescents at Santu Petrus Catholic High School Pontianak. Quantitative research design using a cross-sectional descriptive approach. The sampling technique is simple random sampling and the sample of this study is 245 students of Santu Petrus Pontianak Catholic High School for the 2023-2024 school year. The research instruments used were the Educational Stress Scale for Adolescent questionnaire and the Gastritis questionnaire. Bivariate data analysis used the Chi Square test to determine the relationship between academic stress levels and the incidence of gastritis at Santu Petrus Catholic High School Pontianak. The results of this study showed that the incidence of gastritis was 86 respondents (35.1%) and the majority of the levels of academic stress were moderate with 209 respondents (85.3%). From the chi square test , p-value = 0.016 (<0.05), then Ha is accepted, which can be interpreted that there is a relationship between the level of academic stress and the incidence of gastritis in adolescents at Santu Petrus Catholic High School Pontianak. In this study, there is a relationship between the level of academic stress and the incidence of gastritis in adolescents at Santu Petrus Catholic High School Pontianak. Keywords: Academic Stress, Adolescents, Gastritis, Senior High School